Smashed [videorecording (DVD)] - Ponsoldt, James; Ponsoldt, James; Winstead, Mary Elizabeth; Paul, Aaron, 1979-; Mullally, Megan; Place, Mary Kay; Offerman, Nick, 1970-; Spencer, Octavia (Sony Pictures Home Entertainment, 2013)
Kate and Charlie are a young married couple whose bond is built on a mutual love of music, laughter and drinking--especially the drinking. When Kate's drinking leads her to dangerous places and her job as a school teacher is put into jeopardy, she decides to join AA and get sober. Her new lifestyle calls into question whether or not her relationship with Charlie is built on love, or just a boozy diversion from adulthood.